A case of nodular fasciitis that was difficult to distinguish from sarcoma. (2019) - Nagano, Hisato; Kiyosawa, Tomoharu; Aoki, Shimpo; Azuma, Ryuichi
Highlights: Nodular fasciitis is difficult to distinguish from sarcoma. Clinical and pathological findings may not correspond, as in our case. If sarcoma cannot be excluded, treatment should consider the risk of malignancy. Abstract: Introduction: Nodular fasciitis is a reactive proliferative lesion. It is often difficult to distinguish from sarcoma, such as malignant peripheral nerve sheath tumor (MPNST). Therefore, both pathological findings and clinical features must be considered. Presentation of case: A 75-year-old man presented with a 1 × 1 cm mass on his left forearm that had enlarged rapidly without specific symptoms. Magnetic resonance imaging revealed a mass adjacent to brachioradialis. The lesion showed iso-intensity to muscle on T1-weighted images and hyperintensity on T2-weighted images. We made a clinical diagnosis of nodular fasciitis. Under observation, the mass gradually decreased in size and disappeared after two months. Four years later, another lesion appeared at the same site. We performed total excisional biopsy and histopathological examination indicated low grade MPNST or recurrent nodular fasciitis. Since malignancy could not be excluded, wide resection was performed. At 4 years postoperatively, there has been no recurrence. Discussion: In this patient, nodular fasciitis of the right forearm was diagnosed clinically and showed spontaneous regression. However, recurrence was noted after four years. While the clinical features suggested recurrent nodular fasciitis, pathological findings indicated the possibility of low grade MPNST. Conclusion: When it is difficult to determine whether a lesion such as nodular fasciitis is benign or malignant, the patient should be managed by considering the possibility of malignancy.